Burnout Syndrome Amongst Medicine Students in Lithuania and Germany - Rudinskaitė, Ieva; Mačiūtė, Eglė; Gudžiūnaitė, Giedrė; Gerulaitytė, Greta (Acta medica Lituanica, 2024)
Background. The research provides comparative analysis of the burnout syndrome among medical students in Lithuania and Germany and determines relations between burnout and lifestyle, health complaints and seeking for psychological help.Materials and methods. The research was conducted in April 2019 using an anonymous self-administered e-based questionnaire. The sample size was 261 medical students (age mean 20,5 ± 1,8, 46 males, 215 females): 131 from Vilnius University (VU), 67 from Lithuanian University of Health Science (LSMU) and 63 from Heidelberg University (HU), Germany. The 15 items MBI-SS scale was used to identify burnout syndrome among students (Cronbach α =0,74). Emotional exhaustion (>14), cynicism (>6), and professional efficacy (
Keywords: burnout; medical students; stress